2017
DOI: 10.1109/tdsc.2015.2433252
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Automated Software Diversity—Program Evolution Redux

Abstract: The software monoculture favors attackers over defenders, since it makes all target environments appear similar. Code-reuse attacks, for example, rely on target hosts running identical software. Attackers use this assumption to their advantage by automating parts of creating an attack. This article presents large-scale automated software diversification as a means to shore up this vulnerability implied by our software monoculture. Besides describing an industrial-strength implementation of automated software d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…We found that many MTD works only consider (and show) the improvement in regards to security and either assuming that it has no impact on performance or ignore that aspect altogether. We will now discuss the details [62], [65], [75], [69], [127], [100], [70], [59], [146], [61], [65], [76], [66], [91], [71], [78], [79], [80], [147] [64], [94], [143] [72], [67] [85], [7], [58], [107], [68], [131], [118], [77], [141] [105], [109], [73] Works in bold explicitly consider diversity of configurations.…”
Section: A Qualitative Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that many MTD works only consider (and show) the improvement in regards to security and either assuming that it has no impact on performance or ignore that aspect altogether. We will now discuss the details [62], [65], [75], [69], [127], [100], [70], [59], [146], [61], [65], [76], [66], [91], [71], [78], [79], [80], [147] [64], [94], [143] [72], [67] [85], [7], [58], [107], [68], [131], [118], [77], [141] [105], [109], [73] Works in bold explicitly consider diversity of configurations.…”
Section: A Qualitative Evaluationmentioning
confidence: 99%
“…In order to do this, they use a topological distance measure, which in their case is the symmetric difference between the edge sets of the current and the consecutive defense configuration. Although they do not explicitly recognize it as a diversity metric like [109], [73], they bring to light an interesting issue that most MTD papers seem to either miss or assume by default. If there was an attack, that with extremely little modification, could exploit all the defender's configuration that is a part of the MTD, an MTD would not be an effective defense strategy.…”
Section: A) Considers Only Security Of Individual Defenses: Mostmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common (as of 2017) examples of diversity in computer systems are the use of different programming languages, hardware architectures, cloud providers, operating systems, hypervisors, compilers or compiler arguments, and ASLR (Address Space Layout Randomization) versions that enable identical programs to possess diversity. It has previously been argued that there are inherent benefits to software diversity in the context of mitigation of attacks [10,11].…”
Section: Security Through Diversitymentioning
confidence: 99%
“…Until now, however, the ASLR improvements suggested in the literature have suffered from one or more drawbacks that have prevented their use in practice. Some techniques rely on binary rewriting, which does not scale to complex programs such as web browsers [22,38]; others randomize the code using a customized compiler [35], or require each user to download their own unique binary [42].…”
Section: Introductionmentioning
confidence: 99%